Phytoplankton and Physics Chemical Parameters in Estuary Waters, West Coast of South Sulawesi, Indonesia - Samawi, Muh. Farid; Tahir, Akbar; Tambaru, Rahmadi; Amri, Khairul; Lanuru, Mahatma; Armi, Nur Khairunisa (Torani Journal of Fisheries and Marine Science, 2020)
This paper provides an explanation of the condition of phytoplankton in the estuary waters of the west coast of South Sulawesi. The study was carried out on four estuaries namely Tallo, Marusu, Polong and Battoe with spatial sampling from inside the estuary to the outside of the estuary. The results obtained were found in three classes, namely Bacillariophyceae class, Cyanophyceae class, and Dinophyceae class with 19 phytoplankton genera. With an abundance of phytoplankton ranging from 352 - 5304 cells / L, the highest abundance is in the Tallo estuary. Meanwhile, the highest diversity index (H ') was found in Tallo estuary and the highest dominance index (D) was in Tallo estuary. Parameters that characterize high abundance estuaries are nitrate and TSS.